Travel Hopping Enabled Resource Allocation (THEResA) and delay tolerant networking through the use of UAVs in railroad networks - Elias, Yaacoub (2021)
This paper investigates the use of unmanned aerial vehicles (UAVs)/drones for providing high data rates to mobile relays (MRs) placed on top of high speed train wagons, thus introducing the concept of Travel Hopping Enabled Resource Allocation (THEResA). The objective is to provide high data rate connectivity to train passengers in 5G+/6G networks. With the drone flying at the same train speed, highly directive beams can be formed and steered between the drone and each of the MRs. The simulation results in the paper show that this leads to high data rate connectivity, which will be reflected in the indoor links between the MRs and the train passengers inside the wagons. The drones maintain the connectivity to the cellular infrastructure by using high speed links with the cellular base stations (BSs) deployed along the rail track, e.g., through free space optics (FSO). The drones use the BS sites for recharging and resuming their operation. Therefore, a separate set of drones, or the same drones when they are not flying over trains, can be used to provide connectivity to remote rural areas. In fact, high speed trains might travel through rural areas with low population density. Although it is practical to lay fiber optic cables along the rail track, villages and small rural population agglomerations far from the railroad might not have access to the internet backhaul. UAVs can provide this connectivity in a delay tolerant fashion, by heading from the BSs/train station sites towards remote areas, collecting/transferring data from/to these areas, then returning to the sites along the rail track to recharge their batteries. This paper presents an analysis that shows the feasibility of this approach.